Morbidity profile and dynamics of determinants of health-seeking behaviour in geriatric population of Chandigarh, India - Sonia Puri; Praizy Bhandari; N K Goel; Munish Kumar Sharma; Sarabmeet Singh Lehl; Monica Gupta (Wolters Kluwer Medknow Publications, 2022)
Introduction: Aging is a natural process that usually results in physiological, biological, emotional, and financial decline. As a result, a robust health system is required to meet their escalating health needs. Through this study, we got an opportunity to study the morbidity profile of the elderly and to assess their health-seeking behavior and its determinants in urban areas of Chandigarh. Material and Methods: The sample consisted of 360 participants. Multistage and proportionate sampling techniques were used to recruit study subjects. A structured interview was carried out to get information on the different parameters of health-seeking behavior of the elderly population. Results: The most pervasive determinant of health-seeking behavior was perceiving health issues related to age, no family support, and health-care expenditure. Conclusion: The elderly had a positive behavior toward seeking help with regard to health care. Multiple morbidities were evident among the elderly, and modern medication was the greatest choice. Improved perspective toward health, easy accessibility, and awareness regarding the disease may contribute to the willingness of seeking help for the health-care needs.